Types of Family Adopting Orphaned Learners - A Reflection on Challenges and Coping Strategies of Orphaned Learners in Public Primary Schools in Kenya. - Nabwire, Violet Kafwa; Owino, Alice A. (Advances in Social Sciences Research Journal, 2015)
Orphan hood is a depressing status in life and has adverse effects yet every child in Kenya has a right to quality education that should lead to good learning in pursuance to Universal Primary Education (UPE). Majority of orphaned learners are widely affected and fail to attain good performance. However exceptional few perform well and attain high grades enabling them to join good High schools and pursue their academic dreams. The study therefore assessed the types of family set up that host orphaned learners and the coping strategies they device in the new set up. Descriptive survey design was used to collect data from 13 public primary schools with a sample constituting of head teachers, teachers, and orphaned learners. Random sampling technique was used to select the schools; purposive sampling technique choice head teachers and orphaned learners, and random sampling selected teachers. A questionnaire, interview schedule, and document analysis collected the qualitative and quantitative data. Descriptive statistics analyzed the quantitative data and findings were presented in the frequency/mean tables and graphs while qualitative data was presented thematically. The study established that a good number of orphaned learners in Kenya lived with older siblings and received a lot of motivation and encouragement from the sibling that led to their achievement. The second highest number of orphaned learners lived with grandparents who were economically unable to manage the responsibility. The study concluded that majority of orphaned learners lacked guidance from adults and therefore recommended that grandparents who took care of the orphans but not fully financially assisted by the government should be supported, and the Ministry of Health in collaboration with other good will stake holders to launch health and nutrition program in schools where none exists. The findings of the study are important to the government, educational planners, stakeholders, parents and the community.